Determinants of Generation Z’s Purchasing Decisions On Environmentally Friendly Products: Green Perceived Value, Green Trust, And Green Satisfaction - Purwanti, Ika; Nugraha Pratama, Muhammad Adhitya; Sulton, Muhammad; Abadi, Muhammad Dzikri; Sunanik, Sunanik (Kontribusia : Research Dissemination for Community Development, 2025)
This study aims to test and analyze the influence of green perceived value, green trust, and green satisfaction on the purchase decision of environmentally friendly products in Generation Z in Indonesia. This study uses a quantitative method with a survey approach. The population in this study is Gen Z consumers in Indonesia who use Wardah Green Series products in an unknown amount. The sample in this study amounted to 384 people, using a purposive sampling technique. Data was collected using an online questionnaire. Data analysis uses Multiple Linear Regression. The study results show that green perceived value, trust, and satisfaction can increase the purchase decision of Generation Z eco-friendly products.